Low-cost, transportable hydrogen fueling station for early market adoption of fuel cell electric vehicles. (6th July 2015) - Richardson, Ian A.; Fisher, Jacob T.; Frome, Patrick E.; Smith, Ben O.; Guo, Shaotong; Chanda, Sayonsom; McFeely, Mikko S.; Miller, Austin M.; Leachman, Jacob W.
Abstract Thousands of public hydrogen fueling stations are needed to support the early Fuel Cell Electric Vehicle (FCEV) market in the U.S.; as of July 2014 there were 12. Government agencies are the largest investors in the U.S. hydrogen fueling infrastructure and are developing stations that cost anywhere from $1.8–$5.9 million each. To attract private investors and decrease dependence on government funding, a low-cost, mobile hydrogen dispensing system must be developed. This paper describes a transportable 700 bar hydrogen fueling station that has been designed with an off-the-shelf component cost of $423, 000; less than 23% of the capital cost of current stations. The design utilizes liquid hydrogen storage and a novel cryogenic compression system which can be factory built for high volume, rapid production. These stations are contained in a standard 40 foot ISO shipping container to adapt to varying locational demand. The demand adjusted cost to sell hydrogen is estimated to be $9.62/kg. This paper presents the mechanical design and operation of the fueling station. This design won the grand prize for the 2014 Hydrogen Student Design competition and a complete report including an economic analysis and safety features is available elsewhere.